Exogenous application of ALA enhanced sugar, acid and aroma qualities in tomato fruit - Li, Ruirui; Wang, Junwen; Yuan, Hong; Niu, Yu; Sun, Jianhong; Tian, Qiang; Wu, Yue; Yu, Jihua; Tang, Zhongqi; Xiao, Xuemei; Xie, Jianming; Hu, Linli; et al. (Frontiers in Plant Science, 2023)
The content and proportion of sugars and acids in tomato fruit directly affect its flavor ALA enhanced tomato fruit quality quality. Previous studies have shown that 5-aminolevulinic acid (ALA) could promote fruit ripening and improve its aroma quality. In order to explore the effect of ALA on sugar and acid quality during tomato fruit development, 0, 100, and 200 mg L −1 ALA solutions were sprayed on the fruit surface 10 days after pollination of the fourth inflorescence, and the regulation of ALA on sugar, acid metabolism and flavor quality of tomato fruit was analyzed. The results showed that ALA treatment could enhance the activities of acid invertase (AI), neutral invertase (NI), and sucrose synthase (SS), reduce the activity of sucrose phosphate synthase (SPS), up-regulate the expression of SlAI, SlNI and SlSS, change the composition and content of sugar in tomato fruit at three stages, significantly increase the content of sugars in fruit, and promote the accumulation of sugars into flesh. Secondly, ALA treatments increased the activities of phosphoenolpyruvate carboxykinase (PEPC), malic enzyme (ME), and citrate synthase (CS), up-regulated the expression of SlPPC2, SlME1, and SlCS, and reduced the citric acid content at maturity stage, thereby reducing the total organic acid content. In addition, ALA could also increase the number and mass fraction of volatile components in mature tomato fruits. These results indicated that exogenous application of ALA during tomato fruit development could promote the formation of fruit aroma quality and were also conducive to the formation of fruit sugar and acid quality.